The conceptual design of clara, a novel fel test facility for ultrashort pulse generation - Clarke, J; Angal-Kalinin, D; Bliss, N; Buckley, R; Buckle, S; Cash, R; Corlett, P; Cowie, L; Cox, G; Diakun, G; Dunning, D; Fell, B; et al. (2013)
The conceptual design of CLARA, a novel FEL test facility focussed on the generation of ultra-short photon pulses with extreme levels of stability and synchronisation is described. The ultimate aim of CLARA is to experimentally demonstrate that sub-coherence length pulse generation with FELs is viable, and to compare the various schemes being championed. The results will translate directly to existing and future X-ray FELs, enabling them to generate attosecond pulses, thereby extending the science capabilities of these intense light sources. This paper will describe the design of CLARA, pointing out the flexible features that will be incorporated to allow multiple novel FEL schemes to be proven. Copyright © 2013 by JACoW.